Photocatalytic production and biological activity of D-arabino-1,4-lactone from D-fructose - Sho Usuki; Pratiksha Babgonda Patil; Tiangao Jiang; Naoko Taki; Yuma Uesaka; Haru Togawa; Sanjay S. Latthe; Shanhu Liu; Kenji Yamatoya; Kazuya Nakata (Scientific Reports)
Abstract Lactones play crucial roles in various fields, such as pharmaceuticals, food, and materials science, due to their unique structures and diverse biological activities. However, certain lactones are difficult to obtain in large quantities from natural sources, necessitating their synthesis to study their properties and potential. In this study, we investigated the photocatalytic conversion of D-fructose, a biomass-derived and naturally abundant sugar, using a TiO2 photocatalyst under light irradiation in ambient conditions. The resulting products were identified using HPLC, LCMS, MALDI TOF MS, and 1H NMR. The results confirmed the successful production of D-arabino-1,4-lactone as a key product, along with the formation of other valuable compounds, including rare sugars such as erythrose and glyceraldehyde. Analysis of the reaction mechanism revealed that D-arabino-1,4-lactone can be directly produced by the α scission (C1-C2 position cleavage) of D-fructose. Furthermore, erythrose and glyceraldehyde, as rare sugars, can be produced from the decomposition of D-arabino-1,4-lactone, which means that D-arabino-1,4-lactone can be used as a source of rare sugars. Furthermore, to investigate the biological activity of D-arabino-1,4-lactone, it was administered to Bifidobacterium. The results showed that Bifidobacterium proliferated and produced more lactic acid than when cultured in a medium without D-arabino-1,4-lactone, suggesting that Bifidobacterium can utilize D-arabino-1,4-lactone.